Significance of Hyperamylasaemia and Abdominal Pain in Diabetic Ketoacidosis. Issue 5872 (21st July 1973) - Knight, A. H.; Williams, D. N.; Ellis, G.; Goldberg, D. M.
Abstract : An analysis of 35 consecutive episodes of diabetic ketoacidosis confirmed the frequent high levels of serum amylase in this condition. Serum amylase was raised during 21 episodes (60%), and in six instances (17%) the peak level exceeded 1, 000 Somogyi units per 100 ml. Hyperamylasaemia was more often found when the initial blood sugar exceeded 500 mg/100 ml, or when the onset of the episode had been relatively acute (less than 48 hours). There was no conclusive evidence in any patient to support a diagnosis of acute pancreatitis and other explanations for the hyperamylasaemia are discussed. Even grossly raised amylase levels were not associated with increased mortality or morbidity.